2023
DOI: 10.3390/cancers15113055
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Complications of Pan-Cancer Therapies: The Need for Cardio-Oncology

Mengjia Chen,
Jianing Xue,
Maoling Wang
et al.

Abstract: It is more likely that a long-term survivor will have both cardiovascular disease and cancer on account of the progress in cancer therapy. Cardiotoxicity is a well-recognized and highly concerning adverse effect of cancer therapies. This side effect can manifest in a proportion of cancer patients and may lead to the discontinuation of potentially life-saving anticancer treatment regimens. Consequently, this discontinuation may adversely affect the patient’s survival prognosis. There are various underlying mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 128 publications
0
3
0
Order By: Relevance
“…Otherwise, myocarditis could have occurred after infiltrating the inflammatory cells into the myocardium. Therefore, cardio-oncology is designed to assess and treat cardiotoxicity initiated by anticancer agents (9). complications in patients under chemotherapy.…”
Section: A Short Look At the Cardio-oncologymentioning
confidence: 99%
“…Otherwise, myocarditis could have occurred after infiltrating the inflammatory cells into the myocardium. Therefore, cardio-oncology is designed to assess and treat cardiotoxicity initiated by anticancer agents (9). complications in patients under chemotherapy.…”
Section: A Short Look At the Cardio-oncologymentioning
confidence: 99%
“…Conversely, patients with endometrial cancer showed a very high risk of dying from CVDs at the first year after diagnosis, which remains elevated compared to other cancer sites [ 9 ]. Cardiotoxicity, in turn, is a recognized side effect of anticancer treatments that can ultimately lead to therapy discontinuation in some oncological patients [ 10 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, an examination of recent research elucidating the involvement of WT1-associated protein (WTAP) in oncogenesis and its potential therapeutic implications was undertaken [11]. Another article reviews the current epidemiology and mechanisms of cardiac toxicity in pan-cancer therapies, stressing the importance of assessing relevant risk factors [12].…”
mentioning
confidence: 99%